Level of kayakers` skills influence their boat acceleration time series - Karami, E.; Sanjari, M. A.; Boozari, S.; Sarshin, A. (German Journal of Exercise and Sport Research, 2023)
Paddler ability in kayaking is reflected through boat motion. Through the application of accelerometers, an easy to use and readily available assessment tool, the current study attempts to determine whether skill level can be ascertained through such measures in order to better assess performance and training. In all, 79 male canoe sprint kayakers participated in this study and paddled a 200m straight course. According to the time they finished the course, they were divided into three skill level groups and labelled as slow, moderate, and fast speed. Tri-axial boat acceleration data were recorded using an accelerometer system mounted on the back of the kayak. The maximum and standard deviation of boat acceleration along superoinferior, mediolateral, and anteroposterior axes were compared among the three groups. Mixed analysis of variance (ANOVA) test revealed that maximum and standard deviation of acceleration data along the superoinferior axis were significantly greater in the fast speed group than in the moderate and slow ones, and higher in the moderate group than in slow one. These findings suggest that the kayaker`s body movements will eventually be reflected in the boat`s total acceleration, which could be a measure of overall performance. Given that accelerometers are a small, portable, and easy-to-use devices, and that the results of this study also revealed that boat acceleration differs between different skill groups, it appears that studying acceleration time series in real competition and outside of laboratory environments could open a new window into kayak research.